2021
DOI: 10.1161/circheartfailure.120.008166
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Natriuretic Response to Furosemide Stress Test During Acute Heart Failure

Abstract: Background: Poor natriuresis has been associated with a poorer response to diuretic treatment and worse prognosis in acute heart failure. Recommendations on how and when to measure urinary sodium (UNa) are lacking. We aim to evaluate UNa quantification after a furosemide stress test (FST) capacity to predict appropriate decongestion during acute heart failure hospitalization. Methods: Patients underwent an FST on day-1 of admission, and UNa was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 24 publications
(61 reference statements)
0
14
0
Order By: Relevance
“…These points reflect a selected cohort of cardiovascular patients for whom fluid depletion may be necessary, such as in patients with pulmonary weaning failure [ 32 ]. Indications for diuretic were left to the physician, but the response to diuretic was evaluated by the evolution of a clinical–biological congestive score [ 22 ]. Even though this score was adapted from previous studies, it was in accordance with the literature that demonstrated congestive score being clinically relevant and associated with outcomes [ 4 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These points reflect a selected cohort of cardiovascular patients for whom fluid depletion may be necessary, such as in patients with pulmonary weaning failure [ 32 ]. Indications for diuretic were left to the physician, but the response to diuretic was evaluated by the evolution of a clinical–biological congestive score [ 22 ]. Even though this score was adapted from previous studies, it was in accordance with the literature that demonstrated congestive score being clinically relevant and associated with outcomes [ 4 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the literature [ 4 , 22 ], we constructed a congestion score based on clinical indicator and biomarkers of congestion: pulmonary rales/crackles (graded between 0 (no), 1 (< 50% of lung) and 2 (> 50% of lung)), peripheral edema (graded between 0 (no), 1 (ankle), 2 (leg) and 3 (body)), B-lines and/or lung ‘comets’ (graded between 0 (no), 1 (more than 2 area) and 2 (diffuse)), and/or pleural effusion (graded between 0 (no), 1 (unilateral) and 2 (bilateral)) on lung ultrasound, and NT-proBNP (N-terminal pro B-type natriuretic peptide) value over 1500 pg mL −1 [ 4 , 22 ]. The positive fluid balance was not a criterion in the clinical congestion score calculation.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations